Foreign exchange interventions: The long and the short of it - Patrick Alexander; Sami Alpanda; Serdar Kabaca (Bank of Canada, 2022)
This paper studies the effects of foreign exchange (FX) interventions in a two-region New Keynesian model where governments issue both short-term and long-term bonds. Imperfect substitutability between bonds gives rise to portfolio balance effects that make FX interventions effective. Empirically, foreign central banks intervene in both short-term and long-term US bond markets, and therefore modelling interventions in both is critical. We calibrate the model using data for the United States and a foreign region (its trade partners), and then simulate FX interventions made by the foreign region. We find that FX interventions do not have standard beggar-thy-neighbor consequences in our model. Interventions in short-term bonds lead to lower GDP in both regions, while interventions in long-term bonds lead to higher GDP in both regions. These results are driven by the impact of the interventions on the term premium channel, which dominates the trade balance channel in our model.
Keywords: F31; F33; F41; 330; Business fluctuations and cycles; Exchange rates; Exchange rate regimes; Foreignreserves management; International financial markets; International topics